The relationship between organisation strategy and the organisational design : the case of the Department of Justice and Constitutional Development (Western Cape Region) - Hendricks, Ronda Joy (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPA)--Stellenbosch University, 2021.